Tinjauan Hukum Islam tentang Praktik Jual Beli Sayur Melalui Wakālah di Desa Krisik Ponorogo - M. Harir Muzakki; Siti Nurhayati (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2016)
The article seeks to analyze the transaction of vegetables through wakālah method in Krisik Village Ponorogo from Islamic legal perspective. Wakālah requires four important elements: the person who gives a trust (muwakkil), the trustee (muwakkal or wakīl), the deed (muwakkal fīh), and the transaction statements (ijāb-qabūl). The transaction of vegetables in Krisik Village is done in an unusual way. In many areas, the brokers usually buy all farmersâ€™ crops at once and pay for the farmers in-cash. In Krisik Village, the brokers, however, first of all, sell farmersâ€™ vegetables into markets. The brokers will pay the farmers for their vegetables afterward. It means that the brokers do not pay for the farmers in-cash. It is also found that the farmers and brokers in Krisik Village make an uncommon agreement ('aqd), in which they agree to reduce the scale. The practice seems to violate a number of Quranic verses, which ask people to enhance the scales. Such a practice of reducing scale has been a